Cdc42 is required for EGF-stimulated protrusion and motility in MTLn3 carcinoma cells - El-Sibai, Mirvat (2007)
Cdc42 plays a central role in regulating the actin cytoskeleton and maintaining cell polarity. Here, we show that Cdc42 is crucial for epidermal growth factor (EGF)- stimulated protrusion in MTLn3 carcinoma cells. When stimulated with EGF, carcinoma cells showed a rapid increase in activated Cdc42 that is primarily localized to the protruding edge of the cells. siRNA-mediated knockdown of Cdc42 expression caused a decrease in EGFstimulated protrusion and reduced cell motility in timelapse studies. These changes were correlated with a decrease in barbed-end formation and Arp2/3 localization at the cell edge, and a marked defect in actin filament branching, as revealed by rotary-shadowing scanning electron microscopy. Upstream of Arp2/3, Cdc42 knockdown inhibited EGF-stimulated activation of PI 3- kinase at early (within 1 minute) but not late (within 3 minutes) time points. Membrane targeting of N-WASP, WAVE2 and IRSp53 were also inhibited. Effects on WAVE2 were not owing to Rac1 inhibition, because WAVE2 recruitment is unaffected by Rac1 knockdown. Our data suggest that Cdc42 activation is crucial for the regulation of actin polymerization in carcinoma cells, and required for both EGF-stimulated protrusion and cell motility independently of effects on Rac.